Blood cells : a practical guide - Bain, Barbara J. (Hoboken, NJ : Wiley Blackwell, 2022)
In the newly revised Sixth Edition of Blood Cells: A Practical Guide, expert haematologist Barbara J. Bain delivers a guide for use in the diagnostic hematology laboratory, covering methods of collection of blood specimens, blood film preparation and staining, the principles of manual and automated blood counts, and the assessment of the morphological features of blood cells. The book functions well as both a straightforward and practical bench manual and as a reference source for practicing hematologists. It has been completely updated to incorporate newly published information and 400 high-quality photographs to aid in blood cell identification. The text is comprehensive and fully supported by references. A companion website contains multiple-choice questions to aid the reader in retaining the information contained within. While the book provides additional guidance on further tests that should be performed for specific provisional diagnoses, the main focus of the text remains on microscopy and the automated full blood count
Blood sampling and blood film preparation and examination -- Performing a blood count -- Morphology of blood cells -- Detecting erroneous blood counts -- Normal ranges -- Quantitative changes in blood cells -- Important supplementary tests -- Disorders of red cells and platelets -- Disorders of white cells
Includes index
Keywords: Blood Cell Count; Blood Cells -- physiology; Hematologic Tests -- methods; Electronic books